Synthesis and Characterization of Multinuclear Complexes with Pyridylthiolato Selenium (IV) and their Adducts with Neutral Ligands - Wajida L Alhamadani; Nabeel H. Buttrus (College of Education for Pure Sciences, 2006)
Selenium metal react with di-pyridyl disulfide (Py2S2) in refluxing toluene to give the compound [Se(Spy)4] through oxidative addition reaction. Multinuclear complexes of the general formula [Se(Spy)4(MCl2)2] and [Se(Spy)4(MCl2)4J were prepared by a direct reaction of CoCl2.6H2O, NiCl2,6H2O or CuCl2-4H2O with the selenium compounds. Adducts of trinuclear complexes with 1,10-phenanthroline were also prepared and having the general formula [Se(Spy)4(MCl2)2(Phen)2]. The prepared complexes and their adducts were characterized by their metal analysis, IR and UV/Vis spectroscopy, conductivity and magnetic measurements.